Handbook of experimental finance - Füllbrunn, Sascha; Haruvy, Ernan; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2022)
"Offering an in-depth overview of the field's past, present, and future, this Handbook provides a comprehensive analysis of the current topics, methodologies, findings, and breakthroughs in research conducted with the help of experimental finance methodology. Suggesting innovative ways of navigating and structuring financial markets, it also showcases the diversity and promise of using experiments in finance. With contributions from leading experts, the Handbook begins with a series of investigations into human behavior in financial decision-making, asking methodological questions regarding subject pool choice, cognitive finance, physical and physiological measurement, and research directions. Stressing the dual nature of experimental finance, chapters then relate to market experiments by exploring applied topics, including bank runs, financial accounting and nudging. Finally, it examines experimental tools and methodologies, critical perspectives, roadmaps for implementation, and empirical testing of finance theories. With examples of experiments that test the fundamental theoretical constructs in finance, this Handbook will prove a vital resource to students and scholars of finance, financial economics, and experimental methodology. It will also prove useful to practitioners and policymakers looking to innovate and experiment with their approaches to financial decision-making"--
Contents: Introduction to the handbook of experimental finance / Sascha Füllbrunn, Ernan Haruvy -- Part one basic research -- 1. Current and possible future research directions in experimental finance / Charles Noussair -- 2. Experiments in finance: From no to maybe to yes! / Pascal Kieren, Martin Weber -- 3. The complementarity of experimental and archival finance research / Lucy F. Ackert, Hong Qu -- 4. Physiological measures in experimental finance / Eyal Ert, Abigail Hurwitz, Sven Nolte -- 5. Ambiguity, experience and unforeseen events in experimental finance / Stefan T. Trautmann -- 6. Experimental finance and financial professionals / Sascha Füllbrunn, Christoph Huber, Christian König-Kersting -- 7. Cognitive finance / Ciril Bosch-Rosa, Brice Corgnet -- 8. The perils of a blanket model: Financial anomalies and loss aversion / Eldad Yechiam -- 9. Testosterone and financial risk taking / John Dinsmore, Eric Stenstrom, Marcelo Vinhal Nepomuceno -- 10. On attention to information: The checking paradox / Yefim Roth, Ofir Yakobi -- 11. The double-channeled effects of experienced payoffs in investment decisions / Peiran Jiao -- 12. Investing other people's money / Sascha Füllbrunn, Ola Kvaløy, Wolfgang Luhan -- 13. From the field to the lab: Professionals and bidding aggression / Timo Heinrich, Matthew James Walker -- 14. Coordination games: Escaping the straitjacket / Christos A. Ioannou -- Part two applied research -- 15. Perishable goods versus re-tradable assets: A theoretical reappraisal -- Of a fundamental dichotomy / Sabiou M. Inoua, Vernon L. Smith -- 16. Pairing multi-market theory with experiments / Elena Asparouhova, Peter Bossaerts, Sean Crockett -- 17. The effect of favorable and unfavorable information on asset prices / Charles Noussair, Steven Tucker, Mark Ryan -- 18. Market experiments with multiple assets: A survey / John Duffy, Jean Paul Rabanal, Olga A. Rud -- 19. Individual evolutionary learning and zero-intelligence in -- The continuous d
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; Finance -- Research -- Methodology; Finance -- Handbooks, manuals, etc